RACE MATTERS - Mariana Berbec-Rostas; Soheila Comninos; Mary Miller Flowers; Sue Gunawardena-Vaughn; Michael Heflin; Nina Madsen (Sur: International Journal on Human Rights, 2018)
There have been numerous debates about rising authoritarianism and its impact on democracy and human rights. As a human rights funder whose central goal is to strengthen the resilience of the human rights movement, employing a racial justice lens to all our work is critical, now more than ever. Some have argued that highlighting structural racism and discrimination has shifted the focus away from economic inequality and undermined some of the relevance of the contemporary human rights movement. We contend, however, that deep economic inequality is frequently a reflection of deep inequality in the underlying power structures that govern societies. Employing a racial justice lens offers us the opportunity to deconstruct structures that contribute to a host of rights violations and allows us to gain a deeper understanding of how oppressive structures intersect. This essay is a reflection on some of our learning to date.